Soluble angiotensin-converting enzyme 2: a potential approach for coronavirus infection therapy?. Issue 5 (13th March 2020) - Batlle, Daniel; Wysocki, Jan; Satchell, Karla
Abstract: A new coronavirus, referred to as SARS-CoV-2, is responsible for the recent outbreak of severe respiratory disease. This outbreak first detected in Wuhan, China in December 2019, has spread to other regions of China and to 25 other countries as of January, 2020. It has been known since the 2003 SARS epidemic that the receptor critical for SARS-CoV entry into host cells is the angiotensin-converting enzyme 2 (ACE2). The S1 domain of the spike protein of SARS-CoV attaches the virus to its cellular receptor ACE2 on the host cells. We thought that it is timely to explain the connection between the SARS-CoV, SARS-CoV-2, ACE2 and the rationale for soluble ACE2 as a potential therapy.